Linguagem online: um estudo sobre hashtags na rede social Facebook. - Mendes, Anderson Vitor dos Santos (2022)
The society has undergone strong transformations with the emergence of Digital Information and Communication Technologies (DICTs) based on a proposal to offer the possibility of providing a language with fast and efficient digital characteristics, able to connect people around the world via the internet almost instantaneously, considering asynchronous and synchronous media. In this sense, this work deals with the research on the use of multimodal texts present in the online language, more specifically the hashtags that circulate in the digital social network Facebook. Considering the importance of a linguistic analysis and description of the texts that transit within the online environment, for a better understanding of the production and reading that users perform within this digital space. The general objective of this work is to carry out the linguistic analysis and description of texts that transit within and between online and offline environments, more specifically the digital hashtag genre. Three more specific objectives follow the general objective: i) to present linguistic concepts involving online language through available literatures; ii) understand how translational practices manifest themselves from offline language to online language in hashtags on social networks; iii) describe the linguistic aspects present in hashtags on social networks with the help of Functionalist linguistic theory. In order to achieve the proposed objectives, a theoretical research will first be carried out, addressing issues related to TDICS and online language, digital and multimodality, translational practices and translinguage, and the theory functionalized so that we can then perform the analysis and description of the selected hashtags. In the construction of the theoretical framework are used the works of Barton and Lee (2015) ; Canagarajah (2013), Garcia (2014, 2017) and Wei (2017); Kress (2010), Rojo and Moura (2012), Street (2014), Dudeney, Hockly and Pegrum (2016); Ribeiro (2008, 2018); Givon (1995), Furtado da Cunha (2008)and Neves (2001, 2006); among others. The partial results point to the importance of developing linguistic studies in cyberspaces, as these are spaces for reflection on language and communication. After all, people’s daily lives are increasingly mediated by online language, which causes basic linguistic concepts to change meaning and/or new concepts to appear.